2018
DOI: 10.1259/bjr.20170641
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound: tumour ablation and its potential to enhance immunological therapy to cancer

Abstract: Various kinds of image-guided techniques have been successfully applied in the last years for the treatment of tumours, as alternative to surgical resection. High intensity focused ultrasound (HIFU) is a novel, totally non-invasive, image-guided technique that allows for achieving tissue destruction with the application of focused ultrasound at high intensity. This technique has been successfully applied for the treatment of a large variety of diseases, including oncological and non-oncological diseases. One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 90 publications
1
77
0
1
Order By: Relevance
“…At high intensities, FUS has been used clinically to thermally ablate tumor cells (FUS and Cancer Immunotherapy, Workshop, 2019). Perhaps more importantly at lower intensities FUS has been shown to stimulate an inflammatory response cancer models which can boost the efficacy of immunotherapy (Bonaventura et al, 2019;Curley et al, 2017;Li et al, 2018;Mauri et al, 2018). Low-intensity FUS, has not yet used in cancer therapy, partly due to our limited understanding of its effects and mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At high intensities, FUS has been used clinically to thermally ablate tumor cells (FUS and Cancer Immunotherapy, Workshop, 2019). Perhaps more importantly at lower intensities FUS has been shown to stimulate an inflammatory response cancer models which can boost the efficacy of immunotherapy (Bonaventura et al, 2019;Curley et al, 2017;Li et al, 2018;Mauri et al, 2018). Low-intensity FUS, has not yet used in cancer therapy, partly due to our limited understanding of its effects and mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Classically immunologically "cold" cancers include glioblastomas, ovarian, prostate, pancreatic, and most breast cancers, all extremely resistant to current therapies. FUS can be potentially be used as an adjunct therapy to induce secretion of cytokines/chemokines from 'cold' cancer cells and mediate conversion into a 'hot' tumor responsive to immunotherapy (Curley et al, 2017;Mauri et al, 2018). Of course, more work will be required in a well-controlled cellular model to understand the critical signaling pathways/ molecules and mechanisms necessary for successful clinical translation of this technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical and preclinical studies have demonstrated the possibility to influence immune response against cancer. It has to be said that all the immunomodulation has been described on other tumors and has not been validated in brain tumors [72,73]. The mechanism behind immunomodulation is complex and is related to all the FUS effects ( Fig.…”
Section: Fus Immunomodulationmentioning
confidence: 99%
“…Stable cavitation refers to the oscillation phenomenon in which a microbubble dilates at its syntonous size, creating a liquid flow called microstreams around the microbubbles. When these oscillating microbubbles reach cells, shear stress is generated, enhancing the permeability of the cell membrane 21,22…”
Section: Effects Of Ummdmentioning
confidence: 99%